The aquatic as elemental excess. Issue 3 (November 2019) - Anderson, Jon
Broadly welcoming Peters and Steinberg's ongoing contributions to moving human geography away from the landlocked, this paper emphasises the importance of repurposing the modern language of hydrology to not only move beyond land versus ocean dichotomies, but also resist the urge to dissolve all hydro-worlds into the excessive ocean. The paper argues for defining particular aquatic spaces through their composition by assembled elemental and extraterrestrial features and forces.